Invariant monotone vector fields on Riemannian manifolds - Barani, A.; Pouryayevali, M.R. (Nonlinear analysis, 2009)
Various concepts of invariant monotone vector fields on Riemannian manifolds are introduced. Some examples of invariant monotone vector fields are given. Several notions of invexities for functions on Riemannian manifolds are defined and their relations with invariant monotone vector fields are studied.